2012
DOI: 10.1097/ede.0b013e318258cb05
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Exposure to Amoxicillin and the Risk of Oral Clefts

Abstract: Background Prior studies have suggested an increased risk of oral clefts after exposure to amoxicillin in early pregnancy, but findings have been inconsistent. Methods Among participants in the Slone Epidemiology Center Birth Defects Study from 1994 to 2008, we identified 877 infants with cleft lip with/without cleft palate (CL/P) and 471 with cleft palate alone (CP). Controls included 6952 non-malformed infants. Mothers were interviewed about demographic, reproductive and medical factors, and details of med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 16 publications
(19 reference statements)
5
29
0
5
Order By: Relevance
“…36, 56, 57, 5961 A recent case-control study of 877 case infants with CL+/−CP found a higher rate of first trimester amoxicillin-exposure among mothers of case-infants (n=28) than among mothers of control-infants (OR=2.0, 95% CI 1.0–4.1). 54 A similar finding was seen in an earlier case-control study (n=1374 cases); a statistically significant association between amoxicillin exposure and CL+/−CP (n=7) was observed. The prevalence odds ratios were 15.9 (95% CI 4.9–51.2) when compared to population controls and 5.4 (95% CI 1.9–15.4) when compared to malformed controls.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…36, 56, 57, 5961 A recent case-control study of 877 case infants with CL+/−CP found a higher rate of first trimester amoxicillin-exposure among mothers of case-infants (n=28) than among mothers of control-infants (OR=2.0, 95% CI 1.0–4.1). 54 A similar finding was seen in an earlier case-control study (n=1374 cases); a statistically significant association between amoxicillin exposure and CL+/−CP (n=7) was observed. The prevalence odds ratios were 15.9 (95% CI 4.9–51.2) when compared to population controls and 5.4 (95% CI 1.9–15.4) when compared to malformed controls.…”
Section: Resultssupporting
confidence: 86%
“…Although recent reports indicate a possible association of amoxicillin with facial clefts, 54, 55 some of these results reach only borderline statistical significance. 54 In addition, if we assume a doubling of the risk 54 in the context of the estimated birth prevalence for CL+/−CP 146 , the absolute risk of orofacial clefts with exposure to amoxicillin would still be considered low.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Den første, med over 1 300 pasienter, identifiserte en signifikant økt risiko for åpen leppe-gane-spalte etter bruk av amoksicillin i første trimester (OR = 2,0; 95 % KI 1,0 -4,1) og i tredje svangerskapsmåned (OR = 4,3; 95 % KI 1,4 -13,0) og en signifikant økt risiko for isolert ganespalte etter bruk av amoksicillin i tredje svangerskapsmåned (OR = 7,1; 95 % KI 1,4 -36) (18). Funnene var basert på 28 amoksicillineksponerte tilfeller av åpen leppe-gane spalte og 11 tilfeller av isolert ganespalte etter amoksicillineksponering i første trimester.…”
Section: Penicillinerunclassified
“…Its use in early pregnancy may increase the risk of oral clefts. 23 Amoxicillin can be used alone or in combination with other agents as an option for treatment-resistant acne. 24 It is associated with gastrointestinal side effects such as nausea and vomiting.…”
Section: Oral Antibioticsmentioning
confidence: 99%